2011
DOI: 10.1111/j.1439-0531.2010.01745.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heavy Metals and Pesticides on Buffalo (Bubalus bubalis) Spermatozoa Functions In Vitro

Abstract: Industrial toxic metals, pollutants and bio-accumulative pesticides interfere with the male reproductive functions in farm animals. Frozen-thawed semen samples were incubated with heavy metals (cadmium and lead) and pesticides (chlorpyrifos and endosulfan) of different concentrations (0, 0.005, 0.05, 0.02, 0.1, 0.5, 1.0, 2.0 and 4.0 μg/ml) for 1 h, and various spermatozoa functional parameters and in vitro fertilization rates were assessed. Any significant effect was assessed by comparing the 1 h data between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…In this study, we have investigated the effects of in vitro exposure to CPF on various functional parameters of bovine spermatozoa (Moce and Graham, ) and examined the possible causes of the alterations observed. Results revealed a significant correlation between in vitro exposure of spermatozoa to CPF and adverse effects on total and progressive motility which are in agreement with sperm reported in humans, bovines and rats (Salazar‐Arredondo et al, ; Selvaraju et al, ; Alaa‐Eldin et al, ).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In this study, we have investigated the effects of in vitro exposure to CPF on various functional parameters of bovine spermatozoa (Moce and Graham, ) and examined the possible causes of the alterations observed. Results revealed a significant correlation between in vitro exposure of spermatozoa to CPF and adverse effects on total and progressive motility which are in agreement with sperm reported in humans, bovines and rats (Salazar‐Arredondo et al, ; Selvaraju et al, ; Alaa‐Eldin et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…In recent years, studies have repeatedly reported that environmental pollutants interfere at different levels with the physiology of organisms, inducing alterations in development and reproduction (Salazar‐Aredondo et al, ; Capriglione et al, ; Perry et al, ; ACOG, ; Tussellino et al, ; Pallotta et al, ). Overexposure to chemical agents, heavy metals and pesticides, present in the environment or introduced into the bodies by feeding, has been demonstrated to reduce sperm quality, acting on spermatozoa counts and lowering percentages of normal mammalian sperm (Selvaraju et al, ; Ebadi Manas, ; Chiu et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of pesticide residues in the fluids surrounding spermatozoa have negative influence on sperm quality (Ghuman et al ,2013) as well as alter spermatozoa chromatin and DNA structure and fertilization competence (SalazarArredondo et al ,2008). These pesticides caused spermatozoa dysfunctions due to their cumulative GroupIII(profenofos+selenium)(n=6) ng/ml effect or their chronic exposure (Selvaraju et al, 2011). Exposure to OPI may cause endocrine changes both directly (as hormone agonists or antagonists) and indirectly (altering circulating levels of hormones by influencing rates of hormone synthesis or metabolism), which can severely affect steroid hormone actions (Moustafa et al, 2007).…”
Section: Pathological Examinationmentioning
confidence: 99%